2014
DOI: 10.1128/jvi.01428-14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Entry Is Impaired by Claudin-1 Downregulation in Diacylglycerol Acyltransferase-1-Deficient Cells

Abstract: Diacylglycerol acyltransferase-1 (DGAT1) is involved in the assembly of hepatitis C virus (HCV) by facilitating the trafficking of the HCV core protein to the lipid droplet. Here, we abrogated DGAT1 expression in Huh-7.5 cells by using either the transcription activator-like effector nuclease (TALEN) or lentivirus vector short hairpin RNA (shRNA) and achieved complete long-term silencing of DGAT1. HCV entry was severely impaired in DGAT1-silenced Huh-7.5 cell lines, which showed markedly diminished claudin-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…HCV pseudoparticles (HCVpp) with E1 and E2 glycoproteins derived from genotype 1a (H77) or genotype 2a (JFH-1) and vesicular stomatitis virus pseudoparticles (VSVpp) were generated as previously described (20). Briefly, HEK293T cells were transfected with the glycoprotein-expressing plasmid, Gag-Pol (polymerase)-packaging plasmid, and transfer vector encoding the firefly luciferase reporter protein by using polyethyleneimine (Sigma-Aldrich).…”
mentioning
confidence: 99%
“…HCV pseudoparticles (HCVpp) with E1 and E2 glycoproteins derived from genotype 1a (H77) or genotype 2a (JFH-1) and vesicular stomatitis virus pseudoparticles (VSVpp) were generated as previously described (20). Briefly, HEK293T cells were transfected with the glycoprotein-expressing plasmid, Gag-Pol (polymerase)-packaging plasmid, and transfer vector encoding the firefly luciferase reporter protein by using polyethyleneimine (Sigma-Aldrich).…”
mentioning
confidence: 99%
“…RNA extraction, cDNA synthesis, and real-time quantitative PCR NK cells were harvested 8 h after PrP C -Fc treatment. Total RNA isolation, cDNA synthesis and TaqMan real-time quantitative PCR were performed as previously described [18]. Briefly, total RNA was isolated using an RNeasy Mini kit (Qiagen, Valencia, CA, USA), and first-strand cDNA was synthesized using a High Capacity cDNA Synthesis Kit (Applied Biosystems, Foster City, CA, USA).…”
Section: Quantification Of Cytokine Productionmentioning
confidence: 99%
“…A number of adverse side effects and the emergence of viral escape mutants are major drawbacks of currently available therapies. Recently, two independent studies have demonstrated that TALEN-based disruption of host genes in liver derived cells inhibits HCV replication and cell entry [24,25]. An APOB -/-Huh-7 stable cell line was established to show that the expression of the apoB-100 protein is necessary for active HCV replication [24].…”
Section: Using Talens To Control Hcv Infection and Replicationmentioning
confidence: 99%
“…An APOB -/-Huh-7 stable cell line was established to show that the expression of the apoB-100 protein is necessary for active HCV replication [24]. Similarly, cell entry and replication cycle of HCV may be obstructed by using TALENs to knock out the diacylglycerol acyltransferase-1 (DGAT1) gene [25]. Although these are interesting observations, the feasibility of using TALENs for treating HCV infection remains to be established.…”
Section: Using Talens To Control Hcv Infection and Replicationmentioning
confidence: 99%